Penentuan Pola Pembelian Obat Pada Apotek Metro Medika Center Pejaten Barat - Feronikawati Lasmaria Sitorus; Agus Salim (LPPM Universitas Bina Sarana Informatika, 2021)
In the business world, data is a very important information company in order to expand and develop its business space. The business world, especially health places such as pharmacies, clinics, and hospitals is demanded to be able to develop and improve their business strategies in drug sales. Pharmacy Metro Medica Center is a Pharmacy located in West Pejaten that still uses manual methods, with each transaction must be written in a ledger, this causes difficulties because so much transaction data exists and it will be difficult to find previous data, and there will be a possibility the data is lost because it is still manual. With the development of technology, it is necessary to process large data by using Data Mining with the Association method. This research was conducted by applying the apriori algorithm by looking at drugs/items that meet the minimum support and minimum confidence. Data mining produces association rules between items in January 2019 until December 2019, known patterns of drug sales. If you buy PARACETAMOL, you will buy AMOXICILLIN and PONSTAN with a support value of 33% and a confidence value of 66.67%.